Modifications of Wind Response of Tall-Building Caused by Interfering Effects: A CFD Approach - Ekanayake, E.M.R.; Herath, H.M.A.I.; Kiriparan, B.; Jayasinghe, J.A.S.C. (The Institution of Engineers, Sri Lanka, 2023)
The wind is an essential factor to consider in the design and construction of tall buildings. As buildings get taller, the wind's impact becomes more significant, and the building's stability and safety become more critical. The interfering effect is one of the significant consequences of a building that needs to be considered. The "interfering effect" is a phenomenon in wind engineering that occurs when an upstream structure affects the wind load on a downstream building. In the past, most of the studies of interfering effects were done with 2D or 3D simulations, only considering one or two parameters from the shape, height, and angle. Therefore, this research attempts to analyze the interfering effect qualitatively and quantitatively from the upstream building to a selected squareshaped principal building by varying the height of the interfering building with different shapes, namely, circular, cross, and triangular shapes with different orientations based on 3D CFD modeling. The commercial CFD package Midas NFX is used for this numerical analysis. The results from the base moment and base shear suggest that a safety factor for interfering effects should be considered in designing the building structures in the city area to ensure the stability of the building, and it is, for the worst-case scenario, 1.3. The pressure fluctuation results highlighted the importance of designing the connection of the cladding system to both compression and tension forces. The findings of the present paper will be crucial in ensuring the stability and safety of the building structures when those buildings are in a dense building environment.
Keywords: CFD Simulation; Interfering effect; Turbulence model; Wind response; Wind tunnel test